HUBUNGAN INFEKSI PROTOZOA USUS DENGAN KANKER KOLOREKTAL: SEBUAH TINJAUAN SISTEMATIS - Rifa, Farras Zahra; Nofita, Eka; Rusjdi, Selfi Renita; Hasmiwati, Hasmiwati; Khambri, Daan; Fadrian, Fadrian (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Colorectal cancer is the third most common malignancy worldwide. Chronic inflammation, including intestinal protozoan infection, is linked to its risk. This systematic review examined the association between protozoan infection and colorectal cancer. Literature was searched in five databases (2014–2024), screened with PRISMA, and assessed using the JBI checklist. Thirty-two studies were reviewed. Protozoan infection incidence was generally higher in colorectal cancer than in non-cancer or other cancer groups. Blastocystis sp. was the most common species. Eighteen of 22 studies showed significant associations, particularly with Blastocystis sp., Cryptosporidium sp., Pentatrichomonas hominis, and Entamoeba histolytica. Factors involved included demographics, biology, environment, lifestyle, clinical history, and cancer stage. Most studies support a significant link. Opportunistic protozoan infections may worsen colorectal cancer progression, and chronic Cryptosporidium infection may induce preneoplastic lesions.